Cutaneous/subcutaneous RREB1::MRTFB fusion-positive extra-glossal mesenchymal neoplasm-two cases expanding the anatomical spectrum of an emerging entity - Důra, Miroslav; Baněčková, Martina; Rozkoš, Tomáš; Michal, Michal; Michal, Michael; Kastnerová, Liubov (Virchows Archiv, 2025)
RREB1::MRTFB fusion-positive extra-glossal mesenchymal neoplasm is a recently recognized tumor so far mostly described in the head and neck area and in the mediastinum. At least some of these neoplasms are potentially related to ectomesenchymal chondromyxoid tumor of the tongue since they share an identical gene fusion and overlapping morphological features in some cases. Herein we describe for the first time two cases with RREB1::MRTFB fusion located in the skin and subcutis. The cases occurred in 36-year-old male with a cutaneous mass on the nose and in 65-year-old woman with a large subcutaneous mass involving the lower leg. Histopathologically, both cases consisted of bland ovoid cells in a myxoid stroma. Immunohistochemically, one of the two cases showed diffuse S100 positivity. RREB1::MRTFB fusion was confirmed in both cases. In summary, the two reported cases expand the anatomical spectrum and improve our understanding of this rare emerging entity.
Keywords: RREB1::MRTFB fusion; Ectomesenchymal chondromyxoid tumor; Extra-glossal mesenchymal neoplasm